The Climate Comic / Comic yr Hinsawdd: Tales between generations / Cenedlaethau’n rhannu straeon - Merryn Thomas (Swansea University, 2023)
Comics (sequential art) provide a frame to tell and understand stories and are suited to exploring complex, place-based, and time dependent ‘wicked’ issues. Social interaction and artistic co-creation offer direct health/wellbeing benefits. Climate change is the ‘single biggest health threat facing humanity’(WHO, 2021) and older people are particularly vulnerable today, younger people in the future. We want to give voice to older and younger generations as agents of change, understand experiences, traditions of sustainable behaviours, and offer visions for the future. This bilingual picture book promoting intergenerational work, can generate solidarity, debate, and knowledge sharing.